The Influence of Product Layout on Purchasing Decisions at Alfamidi Minimarket Depok Lima, Desa Poka, Teluk Ambon District - Facey, Rumi; Rehatta, Geradin; Sinay, Francisca Riconita (Universitas Pattimura, 2025)
This study aims to analyze the effect of product layout on purchasing decisions at Alfamidi Minimarket in Desa Poka. In this research, product layout is examined through three main indicators: room space allocation, placement of tables and chairs, and product positioning. Meanwhile, purchasing decisions are measured through several stages, including problem recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. The method used in this research is a quantitative approach utilizing simple linear regression to assess the relationship between the independent variable (layout) and the dependent variable (purchasing decisions). The results show that product layout has a positive and significant influence on purchasing decisions, contributing 34.3%. This finding indicates that a well-organized product layout can enhance shopping convenience, encourage impulse buying, and ultimately, increase customer satisfaction